The role of macrophages in right ventricular remodeling in experimental pulmonary hypertension. (19th July 2022) - Gu, Sue; Mickael, Claudia; Kumar, Rahul; Lee, Michael H.; Sanders, Linda; Kassa, Biruk; Harral, Julie; Williams, Jason; Hansen, Kirk C.; Stenmark, Kurt R.; Tuder, Rubin M.; Graham, Brian B.
Abstract: Right ventricular (RV) failure is the primary cause of death in pulmonary hypertension (PH), but the mechanisms of RV failure are not well understood. We hypothesized macrophages in the RV contribute to the RV response in PH. We induced PH in mice with hypoxia (FiO2 10%) and Schistosoma mansoni exposure, and in rats with SU5416‐hypoxia. We quantified cardiac macrophages in mice using flow cytometry. Parabiosis between congenic CD45.1/.2 mice or Cx3cr1‐green fluorescent protein and wild‐type mice was used to quantify circulation‐derived macrophages in experimental PH conditions. We administered clodronate liposomes to Sugen hypoxia (SU‐Hx) exposed rats to deplete macrophages and evaluated the effect on the extracellular matrix (ECM) and capillary network in the RV. In hypoxia exposed mice, the overall number of macrophages did not significantly change but two macrophage subpopulations increased. Parabiosis identified populations of RV macrophages that at steady state is derived from the circulation, with one subpopulation that significantly increased with PH stimuli. Clodronate treatment of SU‐Hx rats resulted in a change in the RV ECM, without altering the RV vasculature, and correlated with improved RV function. Populations of RV macrophages increase and contribute to RV remodeling in PH, including through regulation of the RV ECM.